Caracterización funcional de factores de transcripción implicados en morfogénesis y patogenicidad en especies de Verticillium - Sarmiento Villamil, Jorge Luis (UMA Editorial, 2017)
The soildborne pathogen Verticillium dahliae poses a threat to many important crops worldwide. V. dahliae produces highly durable structures, the microsclerotia, which germinate in the presence of root exudates from the host, producing hyphae that penetrate the root cortex. Upon reaching the xylem, a combination of sporulation and filamentous growth is thought to contribute to vascular colonization. A number of genes have been identified whose alteration affects both virulence and microsclerotium development. This led to postulate that these processes are inextricably linked and co-regulated. Two major signalling pathways, MAPK cascades and cAMP signalling, have been implicated in the regulation of morphogenesis and virulence in fungi. In this work, we functionally characterized three regulatory proteins which are potential downstream targets of these regulatory pathways, revealing that microsclerotium development and virulence can be fully uncoupled. Thus, deletion of the APSES transcription factor (TF) gene vst1 abolished microsclerotium production and altered sporulation processes but did not diminish the ability of the fungus to colonize the host. By contrast, deletion of vph1, a putative homolog of the major target of MAPK signalling ste12, did not affect vegetative growth but rendered strains avirulent. Deletion of vhb1, encoding a protein similar to homeobox TFs involved in sporulation and putative targets of cAMP signalling, greatly impacted sporulation but not microsclerotium development and also rendered strains avirulent. Confocal microscopy showed that ∆vph1 could not penetrate the root cortex while ∆vhb1 was impaired in its ability to proliferate in the xylem.
Interestingly, a microarray analysis identified an important overlap in the genes under Vst1 and Vph1 regulation. We propose that different downstream targets allow the fungus to regulate particular aspects of morphogenesis and virulence through the same pathways. The specific role and putative connection with other components of the signalling pathways of each TF characterized will be discussed.
Keywords: Factores de transcripción - Tesis doctorales; Verticillium wilt; Signalling pathways; Transcription factor; Disease cycle; Morphogenesis